Effectiveness of educational intervention based on transtheoretical model in promoting oral health self-care behaviors among elementary students - Isa Mohammadi-Zeidi; Amir Pakpour-Hajiagha; Banafsheh Mohammadi-Zeidi (Isfahan University of Medical Sciences, 2013)
Introduction: Studies have demonstrated the effectiveness of psychological stage-based educational interventions to promote healthy behaviors. This study examined the effectiveness of an educational intervention based on the stages-of-change model in improving oral self-care behaviors among students in Qazvin, Iran.Materials and Methods: In this randomized controlled study, 160 elementary schoolchildren who were in inactive stages were selected from 8 primary schools using multi-stage sampling approach and were assigned to either the control or the intervention group. Data, including demographic variables, transtheoretical model constructs and the modified plaque index, was collected using a questionnaire before and six months after the intervention. The educational intervention consisted of four 45‒60-minute sessions with a focus on attitude change, self-efficacy promotion and decisional balance change, using images, educational clips and special pamphlets in the intervention group. Data were analyzed with chi-squared test, paired t-test, independent t-test and ANOVA, followed by post hoc Scheffé's test, Wilcoxon's test and Mann-Whitney test (α = 0.05).Results: Before the intervention, none of the subjects were in the action and maintenance stage, while after the educational intervention, 26% of the intervention group subjects moved to active stages and the number of pre-contemplation stage subjects was halved (p value = 0.0003). Significant improvements were observed in self-efficacy (p value = 0.0006), process of change (p value = 0.002) and decisional balance (p value = 0.005) in the intervention group. Training based on the stages model was able to significantly decrease the plaque index (p value = 0.0001) and increase self-reported oral care behavior (p value = 0.021).Conclusion: Educational intervention based on stages-of-change model can improve oral health-related behaviors, and clinical oral and plaque indexes among students. Key words: Education, Health behavior, Oral health, Schools, Self-efficacy